O exílio do sagrado: ensaio de ética teológica aplicada ao Direito e ao Estado - Neves Junior, Nerlito Rui Gomes Sampaio (2010)
To live for good or for evil are two aspects of conduct and life of humans that have been analyzed since ancient times, when man is in search of the ideal forms of complete happiness. Ethic is direct1y integral part of that context and not infrequent1y have been strong in larger philosophical, legal and theological debates. Although they are distinct areas, there is a direct interconnection or interdisciplinary field between the subject matter, for the three "science" above. The present work aims to critically examine the ethical, in its theological aspect, highlighting its limits and values, in the current stage of secularization lived by man, making a dialogue with the modem legal normativity. The intention is to collaborate in the development of Public Theology, specifically in the area of relations between theology and law, seeking to exercise the use of a theoretical framework of action, the study of ethics and law. For this, the paper suggests some current issues relevant such as: a) the concept of secularization in its legal dimension, proposed a radical and inadequate separation between the positivism of law and religious and cultural normativity. This should make it possible to establish a dialogical conception between legal positivism and cultural normativity? b) In the study of ethics and law to the theoretical framework will be directed from the theory of communicative action of Jürgen Habermas. In this aspect the author recognizes the importance of culture and religion in shaping contemporary law, without, however, develop the theme. Then it would be possible?